2017
DOI: 10.1002/mrm.26629
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion‐relaxation correlation spectroscopic imaging: A multidimensional approach for probing microstructure

Abstract: Purpose To propose and evaluate a novel multidimensional approach for imaging sub-voxel tissue compartments called Diffusion-Relaxation Correlation Spectroscopic Imaging (DR-CSI). Theory and Methods Multi-exponential modeling of MR diffusion or relaxation data is commonly used to infer the many different microscopic tissue compartments that contribute signal to macroscopic MR imaging voxels. However, multi-exponential estimation is known to be difficult and ill-posed. Observing that this ill-posedness is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
188
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(190 citation statements)
references
References 59 publications
2
188
0
Order By: Relevance
“…Interestingly, only a number of TE repetitions equal to the number of compartments that are assumed to be in the tissue is necessary. This results of the substitution of the ILTs by BSS, in comparison to other techniques . We found a good agreement between the T2IE estimates of the FLAIR multi‐echo SE for 17 TEs and those of BSS for 2 TEs.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Interestingly, only a number of TE repetitions equal to the number of compartments that are assumed to be in the tissue is necessary. This results of the substitution of the ILTs by BSS, in comparison to other techniques . We found a good agreement between the T2IE estimates of the FLAIR multi‐echo SE for 17 TEs and those of BSS for 2 TEs.…”
Section: Discussionsupporting
confidence: 66%
“…Furthermore, our solution is diffusion protocol‐agnostic (only two TEs and one nondiffusion weighted volume are necessary), allowing for flexibility in the design of the acquisition protocol, which might include any number of diffusion directions and b ‐values. This gives it an advantage over diffusion–relaxation correlation techniques based on regularized ILTs …”
Section: Discussionmentioning
confidence: 99%
“…To date, these multidimensional relaxation–diffusion correlation (REDCO) spectroscopy experiments have been primarily relegated to applications involving NMR studies in homogeneous samples (Silva et al, 2002; Galvosas and Callaghan, 2010; Bernin and Topgaard, 2013; Song et al, 2016). However, apart from a few studies (Zhang and Blümich (2014); Tax et al (2017); Kim et al (2017)), these methods have not been widely used in MRI applications owing to the vast amount of scan time and acquired MR data required to reconstruct a single multidimensional spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…With that method, a maximal acceleration factor of 3.5 was achieved, reducing the number of acquisitions from 1,800 to 450, which is still infeasible for clinical MRI applications. A recent spatially resolved REDCO study reported one distinct D - T 2 peak in the WM region and a different distinct peak in the gray matter (GM) region of a spinal cord specimen (Kim et al, 2017). These results, specifically the monocompartmental tissue structure in WM, contradict many previous studies (e.g., Ronen et al (2006); Peled et al (1999); MacKay et al (2006)) and may be due to the very small number of acquisitions, 28, used to reconstruct the D - T 2 spectra, or to the use of spatial regularization.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have proposed methods that do not explicitly impose the number of compartments, but rather derive them from the data . Although prone to overfitting, such methods have been shown to provide good results in problems in which the number of components is difficult to establish a priori, such as crossing fibers or the joint diffusion– T 2 relaxometry quantification …”
Section: Introductionmentioning
confidence: 99%